Surgical contribution to the management of primary hyperparathyroidism - Libánský, P; Adámek, S; Broulík, P; Pafko, P; Pozniak, J; Tvrdon, J (Prague medical report, 2004)
Surgical management of primary hyperparathyroidism is a very effective method. The target is to cure primary hyperparathyroidism and to reach normal calcium levels. This results in an improvement of health condition and resolution or at least moderation of symptoms. Complications are infrequent and mortality is very low. Surgical management is definite, safe and effective. Authors of this article address the diagnosis of primary hyperparathyroidism, clarify bone, metabolic and biochemical syndromes and present series of 151 patients that have been operated on at the 3rd Department of Surgery of the Motol University Hospital, Prague, with the diagnosis of primary hyperparathyroidism. The survey is focused on the primary hyperparathyroidism concomitant diseases and on the possible sequelae in the postoperative period.
Keywords: Parathyroidectomy; Male; Adolescent; Child; dítě; Adult; paratyreoidektomie; Aged; dospělí; mužské pohlaví; senioři; mladiství; hyperparatyreóza; senioři nad 80 let; Hyperparathyroidism; lidé; ženské pohlaví; Humans; Aged, 80 and over; Female; lidé středního věku; Middle Aged